1999
DOI: 10.1093/jn/129.7.1382
|View full text |Cite
|
Sign up to set email alerts
|

High Intake of Milk Fat Inhibits Intestinal Colonization of Listeria but Not of Salmonella in Rats

Abstract: During fat digestion, fatty acids and monoglycerides are liberated in the gastrointestinal tract. Generally, these lipids are potent inhibitors of gram-positive bacteria in vitro but have less effect on gram-negative microbes. Considering this, we hypothesized that increased intake of bovine milk fat would result in enhanced gastrointestinal killing of Listeria monocytogenes (gram-positive) but have little effect on infection with Salmonella enteritidis (gram-negative) in rats. To test this, rats were fed eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Because sphingosine and palmitoyl-D,Lcarnitine had similar structures, with a charged head group coupled to a C 16:0 acyl chain, we further examined the effects of saturated fatty acids on biofilm formation. Although some fatty acids impair the growth of L. monocytogenes (46,48), their effects on biofilm formation have not been reported. Saturated fatty acids with chain lengths ranging from C 9:0 to C 18:0 were tested for their effects on biofilm development (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because sphingosine and palmitoyl-D,Lcarnitine had similar structures, with a charged head group coupled to a C 16:0 acyl chain, we further examined the effects of saturated fatty acids on biofilm formation. Although some fatty acids impair the growth of L. monocytogenes (46,48), their effects on biofilm formation have not been reported. Saturated fatty acids with chain lengths ranging from C 9:0 to C 18:0 were tested for their effects on biofilm development (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent studies have implicated microbially produced fatty acids or derivatives as diffusible signal factors that control, among other phenotypes, biofilm formation by heterologous species (43). Bovine milk, which contains a variety of fatty acids, has been shown to reduce the amount of viable L. monocytogenes cells in vitro, as well as to prevent intestinal colonization of rats in a chain length-dependent manner (46)(47)(48). Sprong et al showed that shorter-chain-length saturated fatty acids (C 4:0 , C 6:0 , and C 8:0 ) lack bactericidal activity toward L. monocytogenes even at 500 M. In addition, neither C 16:0 nor C 18:0 had bactericidal activity at 500 M, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that L. monocytogenes may be better able to colonize the gastrointestinal tract when delivered to animals in a higher-fat vehicle. Sprong et al (34) determined that in rats a diet high in fat inhibits colonization of L. monocytogenes in the gut; however, in their study, L. monocytogenes was administered in a saline solution. This approach is different from our study, where L. monocytogenes was administered in a high-fat vehicle to animals on a normal monkey diet.…”
mentioning
confidence: 99%
“…Stock solutions of bacteria were routinely stored at Ϫ80°C in culture media (listed in Table 2) containing 20% (vol/vol) glycerol. Bacterial cells were cultured as described before (20) using the agar plates, broth, and culture conditions described in Table 2. Bactericidal activity of fatty acids (all obtained from Fluka, Buchs, Switzerland) was tested in citrate buffer at pH 5 (100 mmol of potassium citrate per liter) and 37°C as described before (20).…”
mentioning
confidence: 99%
“…Bacterial cells were cultured as described before (20) using the agar plates, broth, and culture conditions described in Table 2. Bactericidal activity of fatty acids (all obtained from Fluka, Buchs, Switzerland) was tested in citrate buffer at pH 5 (100 mmol of potassium citrate per liter) and 37°C as described before (20). Because the strictly anaerobic bacterium C. perfringens did not survive the washing procedure in an aerobic environment, overnight cultures were directly diluted in sterile saline and immediately placed in an anaerobic cabinet (Coy Laboratory Products Inc., Ann Harbor, Mich.).…”
mentioning
confidence: 99%